Depressive Symptoms Among Children and Adolescents in China During the Coronavirus Disease-19 Epidemic: A Systematic Review and Meta-Analysis - Chen, Jianghe; Yang, Kun; Cao, Yujia; Du, Yun; Wang, Ningqun; Qu, Miao (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic has a significant impact on mental health of children and adolescents. While some published studies have investigated the prevalence of depression among children and adolescents in China during the pandemic, the results vary widely. Based on these previous studies, we aimed to systematically analyze and estimate the prevalence of depressive symptoms among children and adolescents in mainland China during the COVID-19 pandemic and attempt to figure out the reasons for prevalence variety in previous studies. Methods: Published studies focusing on the prevalence of depressive symptoms among children and adolescents during the COVID-19 pandemic were searched in the PubMed, EMBASE, Cochrane CENTRAL, China National Knowledge database (CNKI), the Chinese Scientific Journal Database (VIP Database) and the WanFang database from December 2019 to May 2021. The quality of all included studies was assessed by the Joanna Briggs Institute's critical appraisal checklist for studies reporting prevalence data (JBI) and the AHRQ's cross-sectional study quality evaluation items (AHRQ). Meta-analysis using inverse variance and random-effects modeling, along with sensitivity analyses, were performed to synthesize article estimates. Results: Of the 1708 references screened, 13 related reports involving 41,729 participants met our inclusion criteria. The results suggested that the pooled prevalence of depressive symptoms among Chinese children and adolescents during the COVID-19 epidemic was 28.6%. Subgroup analyses showed that the pooled prevalence of depressive symptoms was highest among the studies using PHQ-9 (46.8%) and lowest among these using DSRSC (11.4%). The pooled prevalence of studies including primary school students was lower (16.5%) than that of studies excluding primary school students (39.1%). Conclusions: The results of our meta-analysis suggest that depressive symptoms were relatively prevalent among Chinese children and adolescents during the COVID-19 epidemic, we should pay more attention to the mental health of them, especially to the secondary school students, and suitable screening tools should be carefully chosen.